Ripartire dai territori: il ruolo dell’artigianato artistico napoletano - Gianfranca Ranisio (EtnoAntropologia, 2014)
This paper analyzes some practices to enhance and promote the artistic Neapolitan handicraft, specifically the  jewelry production, historically situated in Naples,  inside an area specifically called, just because of its economic activities, “Borgo degli Orefici”. Handicraft is a form of technical know-how, a set of acquired and embedded skills, binding a product to specific social and cultural contexts and distinguishing it from industrial production. The artistic handicraft is a proper production of prestige goods, but this production is often in trouble with UE policies and internationalization processes, lacking of organization and synergies. The paper  therefore analyzes the actions promoted by the Comune di Napoli and the Consorzio Antico Borgo degli Orefici, with the specific aim of overcoming the isolation and making a network among different social involved actors. Finally, the paper focuses the practices that aim on one hand to enhance and promote the productive resources in the area, on the other hand to build and redefine the image of the place and Neapolitan jewelry art. This can happen not by  preserving the old craft forms, but enabling the processes of revision and re-functionalization of the assets, in relation to the social and cultural context of the historical center.